Sony Pictures Entertainment, Inc. : a cybersecurity attack from North Korea (C) - Alexander, Meredith (SAGE Knowledge. Cases., 2017)
On November 24, 2014, Sony Pictures Entertainment, a subsidiary of Sony Inc., was the victim of an unprecedented cybersecurity attack launched by North Korean hackers. The attack was a result of the upcoming premiere of Sony's film The Interview, a comedy based on a fictional attempted assassination of North Korean dictator Kim Jong-un. The group responsible subsequently threatened an attack on theaters choosing to show the film. Sony Pictures CEO Michael Lynton must decide whether or not to stop the movie's release, while also protecting Sony's public image, maintaining distributor relations, minimizing revenue loss, and safeguarding employees data from further risk.